KONTRIBUSI KITAB UŞŪL AL-TAKHRĪJ WA DIRĀSAT AL-ASĀNID KARYA MAHMUD AL-THAHHAN DALAM KAJIAN SANAD HADIS - Muhammad Briananda Ridiansyah; Muhid; Andris Nurita; Nikmatil Islamiyah Maghfiroh (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2023)
Uşūl Al-Takhrij Wa Dirasat Al-Asanid is a book that deals with the history and development of Takhrīj Hadith. Although this book discusses the Takhrīj hadith method, some scholars argue that these methods still have limitations in examining the validity of a hadith. This paper aims to elaborate on the Book of Uşūl Al-Takhrīj Wa Dirāsat Al-Asānid, to examine the validity, reliability, and authenticity of the hadith, and to ensure that it really comes from the Prophet Muhammad (peace be upon him). So we need to know the quality of sanad and matan hadith, so as to judge the authenticity of the hadith through the Takhrīj method. This research uses a descriptive-qualitative method, which is to collect and analyze data to help explain all sanad and matan in a hadith. The results of this study show that through the five Takhrīj Hadith Methods described by Mahmud al-Thahhan, by tracing and searching for hadiths from various original books can be used to determine the quality of sahih hadith, dho'if and maqbul. The application of the takhrij method in hadith research is very important and relevant in the shahihan of Hadith. To confirm that a hadith is really from the Prophet (peace be upon him). So to assess a Hadith, researchers and academics have ways and rules that are followed through the rules described by Mahmud al-Thahhan.